Cross-cultural measurement invariance of the online learning readiness self-check (OLRSC) survey: a study across Turkish, Romanian, and Polish college students - Elif Çimşir; Meral Çapar; Ruxandra Folostina; Claudia Iuliana Iacob; Wioletta Tuszyńska-Bogucka; Lidia Mirowska; Aras Bozkurt (Springer, 2024)
Abstract This study examined the factorial composition and cultural invariance of the online learning readiness self-check (OLRSC) survey across Turkish (N = 212), Romanian (N = 207), and Polish (N = 235) college students. The results of confirmatory factor analyses (CFA) in individual samples supported the six-dimensional structure of online learning readiness while measurement invariance testing in a multi-group setting supported the metric and partial scalar invariance of the OLRSC survey. The latent means for the dimensions of online learning preparedness across the three groups were also examined in this study, revealing substantial differences. The results supported that the OLRSC is a psychometrically sound scale that can contribute to the scientific investigation of college students' online learning readiness in the three nations. The findings not only extend the applicability of the OLRSC survey beyond its original U.S. context and atypical learners but also provide valuable insights for educators and policymakers striving to enhance online teaching and learning practices globally.